Smartphones, Wechat and Paid Content: Journalists and Sources in a Chinese Newspaper. (2nd January 2020) - Wang, Dan; Sparks, Colin
ABSTRACT: This article reports on research into the relations between reporters and sources in a Chinese newspaper in a transitional period brought about by the diffusion of smartphones and instant messaging. The article adopts the theoretical framework of political economy, supplemented by elements of the classic sociology of journalism that emphasize the routinized nature of journalist-source relationships. It argues that in the newspaper studied here the nature of that relationship is changing. The article reports on the ways in which technological changes have weakened the link between the reporter and her colleagues in the newsroom, which has been an important source of countervailing pressure to the influence of sources. It also shows how the economic effects of new technologies have forced the newspaper to increase its reliance on paid content and how reporters are expected aggressively to solicit this from their sources. Overall, both the reporters and the newspaper have become much more source-dependent than previously. The article closes with a discussion of how far these findings can be generalized, both within China and more broadly.